Anti-Inflammatory Metabolites in the Pathogenesis of Bacterial Infection - Urso, Andreacarola; Prince, Alice (Frontiers in Cellular and Infection Microbiology, 2022)
Host and pathogen metabolism have a major impact on the outcome of infection. The microenvironment consisting of immune and stromal cells drives bacterial proliferation and adaptation, while also shaping the activity of the immune system. The abundant metabolites itaconate and adenosine are classified as anti-inflammatory, as they help to contain the local damage associated with inflammation, oxidants and proteases. A growing literature details the many roles of these immunometabolites in the pathogenesis of infection and their diverse functions in specific tissues. Some bacteria, notably P. aeruginosa, actively metabolize these compounds, others, such as S. aureus respond by altering their own metabolic programs selecting for optimal fitness. For most of the model systems studied to date, these immunometabolites promote a milieu of tolerance, limiting local immune clearance mechanisms, along with promoting bacterial adaptation. The generation of metabolites such as adenosine and itaconate can be host protective. In the setting of acute inflammation, these compounds also represent potential therapeutic targets to prevent infection.